Evaluation of different orange maturation curves by means of cluster analysis - Junior, Dirceu Mattos; Gonzales, Angela Fuentes; Junior, Jorgino Pompeu; Parazzi, Clóvis (Pesquisa Agropecuaria Brasileira, 1999)
Fruit maturation of seventeen sweet orange clones and cultivars were evaluated by cluster analysis. Soluble solids (°Brix) and acidity were determined during the spring season 1995, in Cordeirópolis, SP, Brazil. Polynomial equations were determined between August and December and values for those variables were estimated 70, 75, 80, 85 and 90 days after the initial fruit sampling. The data set was standardized to perform cluster analysis regarding the Euclidean distance measure and the linkage rule as UPGMA type. Four clusters were selected in regard to fruit maturation stage. Navelência, the earliest clone, showed 13.4°Brix and 0.83% acidity in the beginning of the considered period. The Pêra cultivar, another single clone cluster, showed ratio higher than 12.0 after middle October. The Natal, Folha Murcha, Old Bud Line, Cutter, Valência, Lue Ging Gong and Tuxpan orange clones and cultivars formed a third cluster, which reached harvesting maturity during middle November, whereas, Frost, Whits, Olinda, Late, Stone, Chaffei, Werley and Berry clones reached the same stage forty days later.